PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, INVENTORY TURN OVER DAN RETURN ON ASSET TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Zeze Zakaria Hamzah; Muhlis Muhlis; Nur Kholis; Tyara Pratiwi Poenomoputri; Yolan Cinthia Husen (Institut Teknologi dan Bisnis Dewantara, 2024)
This study aims to examine the effect of Current Ratio, Debt to Equity Ratio, Inventory Turn Over, Return On Asset on stock prices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling method in this study is by purposive sampling method totaling 11 companies. This study uses panel data regression analysis with the help of eviews9 software. The results of this study show that partially the variables Current Ratio, Debt Equity Ratio, Inventory Turn Over have no significant effect on stock prices, while the Return On Asset variable has a positive and significant effect on stock prices. Meanwhile, the results of the simultaneous study showed that the variables Current Ratio, Debt Equity Ratio, Inventory Turn Over, Return On Asset had an effect and were significant on the stock price of companies in the food and beverage sub-sector for the 2018-2021 period.